Akibat Hukum Perjanjian Penyelesaian Sengketa Perbankan Syariah (Kajian Terhadap Klausula Pilihan Forum Penyelesaian Sengketa Di Pengadilan Negeri) - Nurul Hasana; Mustopa Mustopa; Enceng Arif Faizal; Syamsul Falah; Dadang Syaripudin (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
This research examines the legal consequences of the choice of forum clause for resolving Sharia banking disputes in the general court in the agreement made by the parties. Prior to the issuance of Constitutional Court Decision Number 93/PUU-X/2012, the parties could determine the clause of choice of forum for resolving banking disputes by litigation through the district court. The research objectives examine 1) the authority of religious courts in adjudicating and resolving Sharia banking disputes before the issuance of Constitutional Court Decision Number 93/PUU-X/2012; and 2) the legal consequences of the choice of forum for resolving Sharia banking disputes in the district court in the agreement before the issuance of Constitutional Court Decision Number 93/PUU-X/2012. This type of doctrinal research uses a conceptual approach and legislation. The technique of analyzing research materials uses a prescriptive approach with the aim of providing arguments for the results of research that has been done. This research concludes that: 1) the choice of forum clause for resolving Sharia banking disputes before the issuance of Constitutional Court Decision Number 93/PUU-X/2012, cannot override the legal provisions related to the absolute competence of religious courts; 2) the legal consequences of the lawsuit for Sharia banking disputes through the district court, either before or after the issuance of Constitutional Court Decision Number 93/PUU-X/2012, the decision on the case must be declared unacceptable (niet ontvankelijke verklaard). Penelitian ini mengkaji akibat hukum klausula pilihan forum penyelesaian sengketa perbankan syariah di peradilan umum dalam perjanjian yang dibuat para pihak. Sebelum keluarnya putusan MK Nomor 93/PUU-X/2012, para pihak dapat menentukan klausula pilihan forum penyelesaian sengketa perbankan secara litigasi melalui pengadilan negeri. Tujuan penelitian mengkaji: 1) kewenangan pengadilan agama dalam mengadili dan menyelesaikan sengketa perbankan syariah sebelum keluarnya putusan MK Nomor 93/PUU-X/2012; dan 2) akibat hukum pilihan forum penyelesaian sengketa perbankan syariah di pengadilan negeri dalam perjanjian sebelum adanya putusan MK Nomor 93/PUU-X/2012. Jenis penelitian doktrinal dengan menggunakan pendekatan konseptual, dan peraturan perundang-undangan. Teknik analisis bahan penelitian menggunakan pendekatan preskriptif dengan tujuan untuk memberikan argumentasi terhadap hasil penelitian yang telah dilakukan. Penelitian ini menyimpulkan bahwa: 1) klausula pilihan forum penyelesaian sengketa perbankan syariah sebelum keluarnya putusan MK Nomor 93/PUU-X/2012, tidak dapat mengesampingkan ketentuan hukum terkait dengan kompetensi absolut pengadilan agama; 2) akibat hukum gugatan sengketa perbankan syariah melalui pengadilan negeri, baik sebelum atau setelah keluarnya putusan MK Nomor 93/PUU-X/2012, maka putusan atas perkara tersebut harus dinyatakan tidak dapat diterima (niet ontvankelijke verklaard).